2010
DOI: 10.1177/1074248410378506
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of L-Arginine in Experimentally Induced Myocardial Ischemia: Comparison With Aspirin

Abstract: L-arginine supplementation represents a potentially novel nutritional strategy for preventing and treating coronary artery diseases especially in cases of aspirin resistance and/or hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
3
4
0
1
Order By: Relevance
“…Reduced NO could promote platelet attachment and release of growth factors in the vessel wall (33). The observed anti-platelet effect of l-arginine, which happens to be in accordance with previous studies (29), may be secondary to increased NOx production. Similar to l-arginine, enalapril significantly reduced platelet aggregation compared to the untreated group; however, levels were still greater than those of the control group.…”
Section: Aortic Intimal Thickness In Nitroglycerin-treated Rabbitsupporting
confidence: 79%
See 1 more Smart Citation
“…Reduced NO could promote platelet attachment and release of growth factors in the vessel wall (33). The observed anti-platelet effect of l-arginine, which happens to be in accordance with previous studies (29), may be secondary to increased NOx production. Similar to l-arginine, enalapril significantly reduced platelet aggregation compared to the untreated group; however, levels were still greater than those of the control group.…”
Section: Aortic Intimal Thickness In Nitroglycerin-treated Rabbitsupporting
confidence: 79%
“…In essence, this realization is in accordance with our previous study, where we demonstrated the cardioprotective domination of l-arginine over the widely used aspirin, in the prevention of myocardial infarction (29).…”
Section: Aortic Intimal Thickness In Nitroglycerin-treated Rabbitsupporting
confidence: 76%
“…Lucotti et al [123] showed that L-arginine-induced a decrease in body weight was due to fat mass reduction when L-arginine was added to a hypocaloric diet and exercise in obese, insulin-resistant type 2 diabetic patients. In addition, a number of experimental and clinical studies have reported the beneficial effects of L-arginine on the serum lipid profile in diabetes including total cholesterol, low-density lipoproteins and triglyceride levels [125][126][127].…”
Section: L-arginine Reduces Obesity: Regulation Of Fat Metabolismmentioning
confidence: 99%
“…In addition, IHD burden the economy [3,4]. Currently, the primary therapeutic methods include percutaneous coronary intervention, coronary artery bypass grafting, and medical therapy [5][6][7][8][9][10][11]. On account of the efficacy and safety of acupuncture, increasing Yulan Ren and Zhihan Chen contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%